The Dependency On Youtube Content Among Culinary Entrepreneurs In Bengkulu City - Riski Putra Utama; Sapta Sari; Indria Indria (Penerbit Jurnal Indonesia, 2023)
Based on the background of the problem, this study aims to determine the dependence of YouTube content among culinary entrepreneurs in Bengkulu City. This research is qualitative. The data collection technique of this research used the method of observation, interviews, and documentation. The theory used in this research is the theory according to Melvin Defluer and Sandra Ball Roceach. (1976) Media Dependency Theory. The results of this study reveal that Culinary Entrepreneurs use YouTube to view recipes and also to fulfill their business needs. Dependence on YouTube content can be seen by their frequent access to YouTube. This culinary entrepreneur's dependence on YouTube is in the form of accessing YouTube every day for eight hours to find information about culinary, both in the form of recipes and cooking tutorials.